Childern’s Completely Attitude to Parents in the Story Book Eating With the Family - Wahyu Sri Lestari, Dian; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Character education is an activity in education to instill good morals in students. One of the characteristics that play an important role in the formation of a child's personality is the character of courtesy. Children who behave politely to their parents and others will behave according to the norms that exist in society. One of the media that can be used to teach manners is storybooks. This study aims to examine the behavior of early childhood manners contained in a storybook entitled Eating with the Family. This research is descriptive qualitative research with a literature review method. Data were obtained from data presentation, documentation, and reading and notes. Then the data were analyzed through data reduction, data presentation, verification, and conclusion. The results obtained are described and adapted to one of the characteristics of early childhood, namely the attitude of courtesy. From the children's storybook Eating with the Family, findings show that there is a polite attitude of children towards parents, firstly the polite attitude of children when entering the house, secondly, the attitude parents' courtesy to children, and thirdly manners when eating together.